Quality parameters and consumer acceptance of pomegranate carrot jelly - Likhitha, P Sree; Swetha, G; Niharika , M (Journal of Postharvest Technology, 2023)
Pomegranate is (Punica granatum) a long lived and drought-tolerant plant. They are widely cultivated in India, Iran and Mediterranean countries.  Pomegranate can help to prevent or treat various disease risk factors such as High Blood Pressure, High Cholesterol, Oxidative Stress and  Hyperglycemia. The Pomegranate fruits are used to prepare Jellies, Candies, Juices, Salads, Smoothies and Yogurt. The present Study is  aimed to develop Pomegranate Carrot Jelly. Carrot is included in this product due to increase of beta-carotene. Carrot’s area unit made in  vitamins, minerals and fiber. They are additionally a decent supply of antioxidants. Carrots may reduce the risk of cancer and support cholesterol  balance & heart health. The Jellies are made with different proportion of ingredients like Pomegranate, Carrot, Sugar, Gelatin & Cardamom. The  Jellies are developed in 3 variations, these variations are evaluated by panel members with organoleptic methods. According to the organoleptic  evaluation results the variation-3 was good. It was concluded that pomegranate is a medicinal fruit and they can include it in their diets could be  benefits for good health.
Keywords: Carrot; jellies; organoleptic evaluation; pomegranate; therapeutic benefits,; variations.